Highlights on Anopheles nili and Anopheles moucheti, Malaria Vectors in Africa (2013)
In this chapter, we review knowledge gained so far on mosquitoes from An. moucheti and closely related species, as well as the An. nili complex. We highlight specific bionomical, ecological and genetic attributes that distinguish these species from the most well-known major African malaria vectors, providing opportunities for further research on neglected aspects of vector biology and control.